2004
DOI: 10.1074/jbc.m305356200
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor-dependent Survival of CESS B Cell Line Is Mediated by Increased Expression and Decreased Degradation of MAPK Phosphatase 1

Abstract: The sIgG ؉ lymphoblastoid B cell line CESS spontaneously produces a high amount of nerve growth factor (NGF) and expresses both high affinity (p140 Trk-A ) and low affinity (p75 NTR ) NGF receptors. Autocrine production of NGF maintains the survival of CESS cells through the continuous deactivation of p38 MAPK, an enzyme able to induce Bcl-2 phosphorylation and subsequent cytochrome c release and caspase activation. In this paper, we show that NGF induces transcriptional activation and synthesis of MAPK phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…3F ). This effect is similar to NGF-induced dephosphorylation of p38 mitogen-activated protein kinase (Torcia et al, 2001;Rosini et al, 2004) and other trafficking proteins such as actin depolymerizing factor (Meberg et al, 1998) and myosin light chain (Fujita et al, 2001). Together, the results demonstrate that HAP1A is phosphorylated in neurons and suggest that the dephosphorylation of HAP1A by NGF relocates it to neurites and their tips.…”
Section: Phosphorylation Of Hap1asupporting
confidence: 59%
“…3F ). This effect is similar to NGF-induced dephosphorylation of p38 mitogen-activated protein kinase (Torcia et al, 2001;Rosini et al, 2004) and other trafficking proteins such as actin depolymerizing factor (Meberg et al, 1998) and myosin light chain (Fujita et al, 2001). Together, the results demonstrate that HAP1A is phosphorylated in neurons and suggest that the dephosphorylation of HAP1A by NGF relocates it to neurites and their tips.…”
Section: Phosphorylation Of Hap1asupporting
confidence: 59%
“…Despite this, there is a report of a non-nuclear localization for this protein. Treating a human lymphoblastic cell line with nerve growth factor increases mkp-1 mRNA synthesis and protein stability (up to 6 h) with a corresponding increase in translocation of the MKP-1 protein to the mitochondrial compartment (Rosini et al, 2004). The significance of this finding awaits further validation.…”
Section: Mitogen-activated Protein Kinase Phosphatase-1 Protein Fumentioning
confidence: 96%
“…Interestingly, MKP-2 is localized specifically in the nucleus, pinpointing the suggestion that specific nuclear activity of JNK is central in JNK-induced apoptosis. 57 Recently, another study showed that the phosphorylation of H2AX by JNK is a very early event in DNA damage-induced apoptosis. 63 Consistent with the idea that H2AX is a substrate for JNK and that γH2AX is required for apoptosis, the authors also described the JNK-dependent pannuclear phosphorylation of H2AX that is proposed to promote the apoptosis of cells subjected to extensive DNA damage.…”
Section: Monographsmentioning
confidence: 99%
“…55,56 Among these phosphatases, MAPK phosphatase 1 (MKP-1) is a cytoplasmic protein that was shown to be down-regulated in cells subjected to translation inhibition induced by severe DNA damage. 57,58 The inhibition of MKP-1 translation therefore releases the negative control of JNK and is proposed to drive JNK activation in these conditions.…”
Section: Other Means Of Jnk Activation By Dna Damagementioning
confidence: 99%